A comparative study of employee characteristics and retention intentions in two private hospitals in Surabaya - Achmad Djunawan; Muhammad Risya Rizki; Emilya Indahyati; Anif Prasetyorini (Berita Kedokteran Masyarakat, 2026)
Purpose: Employee characteristics, well-being, and intention to stay influence workforce stability and performance and may vary across hospitals due to differences in management, work environment, and organizational culture. This study aims to compare employee characteristics (conscientiousness), employee well-being, and intention to stay between two private hospitals in Surabaya, Indonesia. Methods: This study employed a quantitative analytic design with a cross-sectional approach using secondary data collected in December 2024 and January 2025. A total of 228 respondents from Hospital X and Hospital Y participated. Conscientiousness was measured using a structured questionnaire based on the Big Five personality framework; employee well-being was assessed using a multidimensional well-being scale; and intention to stay was measured using indicators of work engagement and organizational commitment. Data were analyzed using the Mann–Whitney U test because the assumption of normality was not met. Results: There was a significant difference in employee conscientiousness between Hospital X and Hospital Y (p = 0.010), with Hospital X showing higher levels. A significant difference was also found in intention to stay (p < 0.001), with employees in Hospital Y reporting stronger retention intentions. In contrast, no significant difference in employee well-being was observed between the two hospitals (p = 0.450). Conclusion: These findings indicate that differences in conscientiousness and organizational context influence employees’ intention to stay in private hospitals. Hospital management is encouraged to adopt personality-informed recruitment and development strategies, alongside strengthening employee well-being programs, as part of hospital human resource policies to enhance workforce retention and sustainability.